Ethnobotanical survey of medicinal and ritual plants utilized by the indigenous communities of Benguet province, Philippines - Janna R. Andalan; Alissa Jane S. Mondejar; Nanette Hope N. Sumaya; Jaime Q. Guihawan; Ma. Reina Suzette B. Madamba; Carlito Baltazar Tabelin; David Guilingen; Florifern C. Paglinawan; Kryzzyl M. Maulas; Isidro Arquisal; Arnel B. Beltran; Aileen H. Orbecido; et al. (Tropical Medicine and Health, 2024)
Abstract Background The Sto. Niño site in Benguet province, Philippines was once a mining area that has now been transformed into an agricultural land. In this area, there has been significant integration of the three indigenous people (IPs) Ibaloi, Kankanaeys and Kalanguyas with the Ilocano community. These IPs safeguard biodiversity and traditional knowledge, including medicinal plant use. However, the documentation of these plant species and their medicinal applications has not been systematic, with the resultant loss of knowledge across generations. This study aims to document the medicinal and ritual plants used by the indigenous communities at the site, in order to preserve and disseminate traditional medicinal knowledge that would otherwise be lost. Methods Ethnobotanical data were collected in Sto. Niño, Brgy. Ambassador, Municipality of Tublay, Benguet, Philippines, and collected through semi-structured interviews, together with focus group discussions (FGD). A total of 100 residents (39 male and 61 female) were interviewed. Among them, 12 were key interviewees, including community elders and farmers, while the rest were selected through the convenience and snowball technique. Demographic information collected from the interviewees included age, gender, and occupation. Ethnobotanical information collected focused on medicinal plants, including the specific parts of plants used, methods of preparation, modes of treatment, and the types of ailments treated. Ethnobotanical quantitative indices of the relative frequency of citations (RFC) and informant consensus factor (ICF) were calculated to evaluate the plant species that were utilized by the community. Results A total of 28 medicinal plants from 20 different families and 6 ritual plants from 5 different families were documented. Asteraceae, Poaceae, and Lamiaceae (10.71%) family are the most mentioned medicinal plant species, followed by Myrtaceae and Euphorbiaceae (7.14%). The most widely used growth form were herbs (46.4%), while leaves (61.5%) were the most utilized plant part, and the preparation of a decoction (62.2%) was the most preferred method of processing and application. The medicinal plants were most commonly utilized for wound-healing, cough and colds, stomachache and kidney trouble, whereas ritual plants were largely used for healing, protection, and funeral ceremonies. Conclusion This study marks the first report on the medicinal and ritual plants used by a group of indigenous communities in Sto. Niño, Brgy. Ambassador, Tublay, Benguet Province. The data collected show that plant species belonging to the Asteraceae, Poaceae, and Lamiaceae family were the most mentioned and should be further evaluated by pharmacological analysis to assess their wider use for medicinal treatment.